Participants at the colloquium on the Spanish Civil War, Barcelona, Palau dels Congresos, 1979, April 19-21. Persons named in debate. Series of 3 photos
Participants at the colloquium on the Spanish Civil War, Barcelona, Palau dels Congresos, 1979, April 19-21. Persons named in debate. Series of 3 photos.